Exploring Immunological Markers In Urinary Tract Infection: An Investigation The Level Of IL6, IL17 And TNF Alpha (The Review of Diabetic Studies, 2025)
Background: Urinary tract infections (UTIs) are frequently caused by bacterial infections, which vary in frequency depending on age and gender. Five percent of all fever cases are caused by it. Infection may be limited to the inferior portion of the urinary tract (UT) or may include the kidney's parenchyma as the first location of bacterial infection.        Aims: This study aimed to evaluate the relationship between the levels of Tumor Necrosis Factor-alpha (TNF-α), Interleukin-6 (IL-6), and Interleukin-17 (IL-8) in UTI cases across various bacterial species.Methodology: A total of 160 urine and blood samples were obtained from UTI patients aged 20 to over 60, along with 65 urine and blood samples from healthy individuals as a control group. After promptly inoculating each urine sample on a blood agar plate and a MacConkey agar plate with a sterile loop, the samples were incubated aerobically for 24 hours at 37°C. To measure the levels of human cytokines (IL-6, IL-17, and TNF-α) in the patient and control groups, an Enzyme-Linked Immunosorbent Assay (ELISA) kit was utilized.Results: Positive bacterial growth was isolated from urine samples, and the results indicated extremely significant differences between the species specified (P